Between as fundation of tragedy in Hölderlin's Empedocles - Másmela Arroyave, Carlos (Estudios de Filosofía, 1994)
The finding of a philosophical innovation present in the term "between" in one of Holderlin's fragments -The foundation according to Empedocles-, constitutes the central idea of the text. In it are resolved the dramatic confliét, the harmonic tension of art and nature, of what is organic and aorgic. It expresses the place where the conflict among these extremes takes place -sacrificial death-, but also the sentiment of intimate reconciliation among the opposites in dispute. Holderlin gives all this porcess a concretion in the figure of Empedocles and the world of being time, an application by means of which he means to clarify the meaning of the tragedy.